A note on intensive fattening of Sudan Desert lambs - Khalafallah, A.M.; El-Khidir, O.A. (1985)
The feedlot performance and carcass characteristics of Sudan Desert lambs under intensive system of feeding and management from birth to 40 kg slaughter weight were investigated. The average daily milk yield of the Watish dams were found to be within the capacity range of intake of the lambs. The dry matter intake during the post-weaning stage were found to be substantially low (4.6 per cent) of the average liveweight of the lambs. Lambs of the Sudan Desert breed could be raised intensively from birth to 40 kg slaughter weight in an average of 180 days.